Controversial and open issues of diagnosis and treatment of myocarditis (based on the discussion of Russian national recommendations) - O. V. Blagova; O. M. Moiseeva; F. N. Paleev (Российский кардиологический журнал)
In October 2020, the Russian Ministry of Health approved clinical guidelines for the management of patients with myocarditis. The aim of this review was to highlight controversial and open issues without unambiguous answer or those that were not described in the paper. The review highlights the objective factors that complicate the development of practical guidelines for the management of this category of patients. Comments on the definition and classification of inflammatory heart diseases are given. The approaches to the diagnosis of patients with suspected myocarditis are discussed. Particular attention is paid to the decision-making strategy in selecting optimal therapy in patients with documented myocarditis and the role of endomyocardial biopsy.